Plantas medicinais e fitoterápicos na Amazônia paraense: elo ancestral entre natureza e saúde para políticas públicas - Melo, Meury da Silva (Universidade Federal de São Carlos, 2024)
Several rural communities value the conservation of nature and its use, managing medicinal plants, handling, and using natural medicines as symbol of their culture. This study aimed to understand the characterization, spatialization and use of medicinal plants and integrative health practices in three municipalities (Bragança, Tracuateua and Augusto-Corrêa, Pará State), in Brazilian Amazon. Based on the content of the “National Policy on Medicinal Plants and Phytotherapeutics” (PNPMF), and on the “National Policy on Integrative and Complementary Practices” (PNPIC, from Brazilian Public Health Service – SUS), we collected data from rural communities and public health entities and professionals. This is an exploratory and descriptive research with mixed qualitative and quantitative methodologies. To identify the species used in the communities, secondary data were used (from lists of species already produced in previous surveys), from 47 rural communities, in the three municipalities. The location of citations was carried out using the Global Satellite Navigation System, the points were imported into QGIS 3.26 and their correspondence to the satellite images contained in Google Earth was verified, to create maps. We had 77 employees from four Basic Health Units involved in the survey (Manoel dos Santos - in Tracuateua, Almoço and Alto-Paraíso – in Bragança, and Buçu – in Augusto Corrêa), from different expertise areas: doctors, dentists, nurses, oral health assistants, community health agents, security guards, drivers, and administrative work professionals. To analyze the use of medicinal plants and the knowledge about them, and the knowledge about public policies, interviews and questionnaires were applied. Thematic maps were prepared with the location of the communities, with the number of species per community, with the characterization of life forms of the identified species, and with the number of species with potential for cultivation. Of the 137 species surveyed, 45% were native. The dominant families were Asteraceae and Lamiaceae. Life forms were herbs (36%), shrubs (30%), trees (28%) and lianas (6%). The ways of obtaining plants in the communities were exchange (33%), cultivation (30%), purchase (22%) and extraction (15%). People in the study area have and afro-indigenous origin and the practice of health care with medicinal plants among them is frequent. No services involving medicinal plants are offered in the public health system. There is no relationship between professionals acting in the public health system and the “healing agents” of the communities, and the public health service employees’ knowledge about the PNPMF and PNPIC is still incipient.
Medicinal plants and phytotherapy in the amazon of pará: ancestral bond between nature and health for public policies
Keywords: Comunidades rurais; Práticas integrativas; Atenção primária à saúde; Agricultura familiar; Agroecologia; PNPMF; PNPIC; SUS; UBS; Rural communities; Integrative practices; Primary health care; Family farming; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL; CIENCIAS DA SAUDE::SAUDE COLETIVA; CIENCIAS BIOLOGICAS::FARMACOLOGIA::ETNOFARMACOLOGIA; CIENCIAS DA SAUDE::SAUDE COLETIVA::MEDICINA PREVENTIVA; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA